Analisis Kesulitan Hasil Belajar Kognitif Siswa Pada Materi Pengaruh Gaya Terhadap Gerak Berdasarkan Hukum Newton Di SMP Negeri 20 Kupang - Herman Yoseph Boro Nimunuho; Alfons Bunga Naen; Maria Ursula Jawa Mukin (Program Studi Pendidikan Fisika Universitas Katolik Widya Mandira, 2023)
The difficulty of learning outcomes in the cognitive domain is a person's inability to remember, understand, apply, analyze, create and evaluate the material that has been explained. The dimensions of knowledge referred to here are factual, conceptual, procedural, and metacognitive knowledge. This study aims to determine student difficulties in working on questions: factual, conceptual, procedural, and metacognitive. This research was conducted at SMP Negeri 20 Kupang. This type of research is descriptive with a qualitative approach. The sample in the study was class VIII E students totaling 30 students. The data collection technique was carried out with a test technique in the form of essay questions totaling 10 items. The results showed that in factual knowledge, students had an average score of 66 with a moderate category of difficulty, conceptual knowledge had an average score of 81 with a category of no difficulty, procedural knowledge had an average score of 26 with a category of great difficulty, and metacognitive knowledge had an average score of 47 with a category of much difficulty.